Re-Interpretasimenstrual Taboo Dalam Al-Qur'an: Menggagas Fiqih Egalitas-Humanis - Mustofa, Mustofa (Musawa Jurnal Studi Gender dan Islam, 2007)
This article is intended to re-exanune and offer a new interpretation to the Qur'anic verses dealing with the issues of menstruation. One of the major problems in the Qur'an is the fact that it is the basic maraji' and mashadir (references) for the formulation of Islamic law and advices on religious matters. In many cases people fail to differentiate between the Qur'an and books of Qur'anic interpretation; the Qur'an has been equated with exegesis of the Qur'an. Further, the Muslim scholars who wrote tafsir are mostly male and live in a patriarchal society, accordingly patriarchal values penetrates into their thoughts. Besides this patriarchal bias in the interpretation, the social realities of Muslims have changed too, in a speed pace. Consequently, the formulation of Islamic fiqh should be changed appropriately to address the current issues, including the idea of menstrual taboo by re-interpreting the Qur'an. This article is therefore not only offering a new light to the interpretation of the text which promotes humanitarian and egalitarian values but also identifying the patriarchal biases in the process of interpreting the Qur'an.